APPLICATION OF HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHY FOR THE ECHINACEA PURPUREA IDENTIFICATION IN DIETARY SUPPLEMENTS AND MEDICINAL PRODUCTS BASED ON IT - Демид, Анна; Вронська, Людмила; Івануса, Ірина; Михалків, Марія (SWorldJournal, 2024)
Medicines and dietary supplements with Echinacea purpurea are presented in the pharmaceutical market of Ukraine. Various ingredients that are obtained from the rhizomes with roots or flowering parts of Echinacea are used in production. Often manufactures